A functional logic for neurotransmitter corelease in the cholinergic forebrain pathway - Nair, Aditya (2023)
The cholinergic system of the basal forebrain plays an integral part in behaviors ranging from attention to learning, partly by altering the impact of noise in neural populations. The circuit computations underlying cholinergic actions are confounded by recent findings that forebrain cholinergic neurons corelease both acetylcholine (ACh) and GABA. We have identified that corelease of ACh and GABA by cholinergic inputs to the claustrum, a structure implicated in the control of attention, has opposing effects on the electrical activity of claustrum neurons that project to cortical vs. subcortical targets. These actions differentially alter neuronal gain and dynamic range in the two types of neurons. In model networks, the differential effects of ACh and GABA toggle network efficiency and the impact of noise on population dynamics between two different projection subcircuits. Such cholinergic switching between subcircuits provides a potential logic for neurotransmitter corelease in implementing behaviorally relevant computations.